Transformasi Ornamen Palais Garnier dengan Teknik Laser Cut dan Iluminasi LED pada Busana Avant-Garde Futuristik - Faldzah Syadwina Putri Prasetya; Irma Russanti (BAJU: Journal of Fashion and Textile Design Unesa, 2026)
The development of avant-garde fashion that integrates art, architecture, and technology encourages the exploration of transforming historical architectural ornaments into futuristic, conceptual, and experimental fashion works. This study aims to examine the design process and final outcome of an avant-garde futuristic garment through the transformation of Palais Garnier architectural ornaments using laser cut techniques and LED illumination. This research employs a quantitative descriptive approach with the Double Diamond design method, consisting of the discover, define, develop, and deliver stages. Data were collected through expert evaluations using a Likert-scale questionnaire covering 13 assessment indicators and analyzed using descriptive statistics. The results indicate that the design process was carried out systematically and achieved a very good level in accordance with the Double Diamond stages. Furthermore, the overall quality of the final garment obtained an average score of 3.28 out of a maximum scale of 4. The findings demonstrate that the transformation of Palais Garnier ornaments through laser cut techniques and integrated LED illumination effectively enhances the futuristic, artistic, and theatrical character of avant-garde fashion.